2019
DOI: 10.3324/haematol.2018.211433
|View full text |Cite|
|
Sign up to set email alerts
|

Recurrent stroke: the role of thrombophilia in a large international pediatric stroke population

Abstract: Risk factors for arterial ischemic stroke in children include vasculopathy and prothrombotic risk factors but their relative importance to recurrent stroke is uncertain. Data on recurrent stroke from databases held in Canada (Toronto), Germany (Kiel-Lübeck/Münster), and the UK (London/Southampton) were pooled. Data were available from 894 patients aged 1 month to 18 years at first stroke (median age, 6 years) with a median follow-up of 35 months. Among these 894 patients, 160 (17.9%) had a recurrence between 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
13
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 31 publications
(15 citation statements)
references
References 38 publications
0
13
0
2
Order By: Relevance
“…Almost 91% of these patients experienced recurrence within the first 6 months after AIS, whereas 45.5% of cases recurred within the first month [36]. A higher prevalence of recurrent stroke was noted by deVeber et al [29] and Sfaihi et al [37], namely 17.9% and 18% from 1 day to 136 months after the first stroke, respectively. In a group of 84 AIS children [38], the median interval to recurrence was 2.3 months and in most observed patients (77%), recurrence occurred within the first 6 months after stroke.…”
Section: Prevalence Of Ais Recurrencementioning
confidence: 83%
See 4 more Smart Citations
“…Almost 91% of these patients experienced recurrence within the first 6 months after AIS, whereas 45.5% of cases recurred within the first month [36]. A higher prevalence of recurrent stroke was noted by deVeber et al [29] and Sfaihi et al [37], namely 17.9% and 18% from 1 day to 136 months after the first stroke, respectively. In a group of 84 AIS children [38], the median interval to recurrence was 2.3 months and in most observed patients (77%), recurrence occurred within the first 6 months after stroke.…”
Section: Prevalence Of Ais Recurrencementioning
confidence: 83%
“…According to an international study by deVeber at al. [29], the following prothrombotic risk factors, i.e., antithrombin deficiency, elevated lipoprotein (a), and the co-existence of more than one prothrombotic factor, were associated with the increase in AIS recurrence risk when adjusting for vasculopathy. The authors observed a single prothrombotic disorder in 269 children with AIS, whereas in 88 patients, more than one prothrombotic risk factor was detected.…”
Section: Thrombophiliamentioning
confidence: 91%
See 3 more Smart Citations